The Influence of Social Media Marketing on Online Shopping Purchase Decisions at PT Chipo Niaga Indonesia - Putra, Mahrezha Nugraha; Mulia, Dipa (Dinasti Publisher, 2024)
Social media marketing in this digital era is widely recognized as an effective tool for connecting with potential customers. PT Chipo Niaga Indonesia is a company specializing in import services from China to Indonesia and has experienced a decline in purchases from 2021 until 2023. This study aims to investigate the influence of various factors on the purchase decisions of PT Chipo Niaga Indonesia's customers. These factors included social media marketing, e-service quality, website quality, perceived price, and trust as an intermediary on purchase decisions of PT Chipo Niaga Indonesia. A quantitative research method using Partial Least Square Structural Equation Modeling 3.0 was employed, surveying 125 consumers of PT Chipo Niaga Indonesia. The findings revealed a surprising result that social media marketing does not significantly impact purchase decisions. These findings suggest that while social media is a popular platform, other factors play more dominant roles in shaping purchase decisions within the context of PT Chipo Niaga Indonesia.